Electrophysiological Evidence for a Direct Link between the Main and Accessory Olfactory Bulbs in the Adult Rat - Vargas-Barroso, Victor; Ordaz-Sánchez, Benito; Peña-Ortega, Fernando; Larriva-Sahd, Jorge A. (Frontiers in Neuroscience, 2016)
It is accepted that the main- and accessory- olfactory systems exhibit overlapping responses to pheromones and odorants. We performed whole-cell patch-clamp recordings in adult rat olfactory bulb slices to define a possible interaction between the first central relay of these systems: the accessory olfactory bulb (AOB) and the main olfactory bulb (MOB). This was tested by applying electrical field stimulation in the dorsal part of the MOB while recording large principal cells (LPCs) of the anterior AOB (aAOB). Additional recordings of LPCs were performed at either side of the plane of intersection between the aAOB and posterior-AOB (pAOB) halves, or linea alba, while applying field stimulation to the opposite half. A total of 92 recorded neurons were filled during whole-cell recordings with biocytin and studied at the light microscope. Neurons located in the aAOB (n = 6, 8%) send axon collaterals to the MOB since they were antidromically activated in the presence of glutamate receptor antagonists (APV and CNQX). Recorded LPCs evoked orthodromic excitatory post-synaptic responses (n = 6, aAOB; n = 1, pAOB) or antidromic action potentials (n = 8, aAOB; n = 7, pAOB) when applying field stimulation to the opposite half of the recording site (e.g. recording in aAOB; stimulating in pAOB and vice-versa). Observation of the filled neurons revealed that indeed, LPCs send axon branches that cross the linea alba to resolve in the internal cellular layer. Additionally, LPCs of the aAOB send axon collaterals to dorsal-MOB territory. Notably, while performing AOB recordings we found a sub-population of neurons (24 % of the total) that exhibited voltage-dependent bursts of action potentials. Our findings support the existence of: 1. a direct projection from aAOB LPCs to dorsal-MOB, 2. physiologically active synapses linking aAOB and pAOB, and 3. pacemaker-like neurons in both AOB halves. This work was presented in the form of an Abstract on SfN 2014 (719.14/EE17).